1975
DOI: 10.1677/joe.0.0670041
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Corticotrophin Analogues in the Blood After Infusion Into Rats

Abstract: An isolated rat adrenal cell bioassay was used to measure blood concentrations in rats after infusion of synthetic human ACTH, corticotrophin-(1-24)-tetracosapeptide or [D-Ser1, Lys17, Lys18]corticotrophin-(1-18)-octadecapeptide amide. Lower blood levels were found with the 1-24 peptide than with human ACTH and the highest levels were found with the 1-18 peptide. These results suggest that the 1-24 peptide which is almost equipotent with natural ACTH in vivo may be more potent at the receptor and corroborate f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

1977
1977
1991
1991

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 10 publications
1
7
0
Order By: Relevance
“…The possibility that potentiating factors prevent ACTH proteolysis is proposed. However, it should be noted that a similar potentiating effect has been demonstrated against modified ACTH-(1-19), whose analogous pep tide, (D-Ser1, Lys17, Lys18) ACTH-(1-18) octadecapeptide amide, is shown to be less susceptible to proteolytic degradation than ACTH-(l-24) [17], The results suggest the existence of mechanisms other than the inhibition of ACTH proteolysis.…”
Section: Discussionmentioning
confidence: 52%
“…The possibility that potentiating factors prevent ACTH proteolysis is proposed. However, it should be noted that a similar potentiating effect has been demonstrated against modified ACTH-(1-19), whose analogous pep tide, (D-Ser1, Lys17, Lys18) ACTH-(1-18) octadecapeptide amide, is shown to be less susceptible to proteolytic degradation than ACTH-(l-24) [17], The results suggest the existence of mechanisms other than the inhibition of ACTH proteolysis.…”
Section: Discussionmentioning
confidence: 52%
“…1975) is con¬ sistent with the more rapid breakdown of Synacthen than of ACTH in in¬ cubated foetal blood (Jones, unpublished observations). For comparison, in the rat in vivo human ACTH130 has a much greater metabolic stability than ACTH!-24 (Synacthen; McMartin 8c Peters 1975;McMartin et al 1977). In the foetus the estimation of metabolic clearance rate is particularly dependent on the position of the infusion and sampling catheters.…”
Section: Discussionmentioning
confidence: 99%
“…This indicated relatively little breakdown of the octadecapeptide by endopeptidases. Consistent with this observation was the survival and relative build-up at 1 h within lysosomes of activity from tritiated octadecapeptide confirming the apparent importance of the kidney in the break¬ down of this peptide (McMartin & Peters, 1975). Interpretation of the quantitative autoradiographic results for the three Synacthen tetracosapeptides tritiated in different positions is not straightforward.…”
Section: Discussionmentioning
confidence: 82%
“…Working with two ACTH analogues, Synacthen (corticotrophin-(l-24)-tetracosapeptide) and C 41795-Ba ([D-Ser1,Lys17,Lys18]-corticotrophin-(l-18)-octadecapeptide amide) and human ACTH, McMartin & Peters (1975) showed that renal ligature of rats significantly decreased the rate of decline of C 41795-Ba and human ACTH following intravenous infusion, but not of the 1-24 peptide. Thus, it would appear that there is a different route for most of the inactivation of the latter analogue.…”
Section: Introductionmentioning
confidence: 99%